The critical role of Th17 cells and IL-17A in autoimmune and inflammation-associated neurological diseases: mechanisms and therapeutic perspectives - Xu Lou, Inmaculada; Zhou, Huifen; Wan, Haitong (Frontiers in Immunology, 2025)
Helper T cells 17 (Th17) and their effector cytokine, interleukin-17A (IL-17A), play a dual role in immune homeostasis. On one hand, they are essential in defense against extracellular pathogens, such as bacteria and fungi, by inducing chemokine production and recruiting neutrophils. On the other hand, their dysregulated activity is strongly linked to autoimmune and inflammatory disorders, including multiple sclerosis, Alzheimer’s disease, Parkinson’s disease, and others. This article reviews the molecular mechanisms regulating Th17 differentiation and function, emphasizing the role of transcription factors like RORγt and RORα, as well as the influence of cytokines such as IL-6, IL-23, and TGF-β. Additionally, it explores the imbalance between pro-inflammatory Th17 cells and regulatory T cells (Tregs), a critical axis in the pathogenesis of autoimmune and neuroinflammatory diseases. In the context of neurological disorders, Th17 cells can infiltrate the central nervous system (CNS), where they contribute to neuroinflammation by activating microglia and astrocytes, exacerbating damage in conditions such as multiple sclerosis, traumatic brain injury, and neurodegenerative diseases. Emerging therapies, including anti-IL-17 monoclonal antibodies and natural modulators, are discussed as potential strategies to restore the Th17/Treg balance without compromising protective immunity. Finally, the need for further research is highlighted to elucidate the specific mechanisms of Th17 infiltration into the CNS, their interaction with the gut microbiota, and the development of personalized therapies. The integration of immunological, metabolic, and environmental approaches offers promising perspectives for the treatment of Th17/IL-17-mediated diseases.